Hubungan Derajat Stres dengan Kejadian Akne Vulgaris pada Mahasiswa Fakultas Kedokteran Unisba Tingkat Dua dan Tiga - Indah Aini; Deis Hikmawati; Gemah Nuripah (Bandung Conference Series: Medical Science, 2023)
Abstract. Acne vulgaris (AV) is a common skin disease, especially in adolescents. Medical students experience more stress than study program students in the non-medical sector. Stress is thought to be one of the components that impact AV by increasing androgen hormones from the adrenal organs and sebum production. The purpose of this study was to determine the relationship between the degree of stress and the occurrence of AV in second and third-grade students of the Faculty of Medicine, Unisba. Method cross-sectional. The number of samples is 100 people with consecutive sampling techniques. Data was collected through the Stress Questionnaire from the International Stress Management Association (ISMA) and AV based on visual assessment through facial photos and observations for the period March-August 2022. Data analysis used the chi-square test. The results showed that of the 5 respondents who experienced mild stress, 4 respondents (80%) experienced AV and 1 respondent (20%) did not experience AV. Then, of the 46 respondents who experienced moderate stress, 22 respondents (47,8%) experienced AV and 24 respondents (52,2%) did not experience AV. Meanwhile, of the 49 respondents who experienced severe stress, 25 respondents (51%) experienced AV and 24 respondents (49%) did not experience AV. P-value = 0,393. The conclusion of this study, there is no significant relationship between the degree of stress and the occurrence of AV. Keywords: Acne vulgaris, adolescents, degree of stress. Abstrak. Akne vulgaris (AV) adalah penyakit kulit yang umum terjadi terutama pada remaja. Mahasiswa kedokteran lebih banyak mengalami stres yang tinggi dibandingkan dengan mahasiswa program studi di sektor non-medis. Stres diduga salah satu komponen yang berdampak pada AV dengan meningkatkan hormon androgen dari organ adrenal dan produksi sebum. Tujuan penelitian ini adalah untuk mengetahui hubungan derajat stres dengan kejadian AV pada Mahasiswa Fakultas Kedokteran Unisba tingkat dua dan tiga. Rancangan penelitian observasional analitik dengan metode cross sectional. Jumlah sampel 100 orang dengan teknik consecutive sampling. Pengambilan data melalui Stress Questionnaire dari International Stress Management Association (ISMA) dan AV berdasarkan penilaian penglihatan melalui foto wajah serta observasi periode Maret–Agustus 2022. Analisis data menggunakan uji chi-square. Hasil penelitian menunjukkan dari 5 responden yang mengalami stres ringan, 4 responden (80%) mengalami AV dan 1 responden (20%) tidak mengalami AV. Kemudian, dari 46 responden yang mengalami stres sedang, 22 responden (47,8%) mengalami AV dan 24 responden (52,2%) tidak mengalami AV. Adapun, dari 49 responden yang mengalami stres berat, 25 responden (51%) mengalami AV dan 24 responden (49%) tidak mengalami AV. Nilai p-value = 0,393. Simpulan penelitian ini, tidak terdapat hubungan yang signifikan antara derajat stres dengan kejadian AV. Kata Kunci: Akne vulgaris, derajat stres, remaja.